Van der Waals cascade in supercritical turbulence near a critical point - Tomohiro Tanogami; Shin-ichi Sasa (Physical Review Research, 2021)
We investigate a quite strong turbulence in a supercritical fluid near a gas-liquid critical point. Specifically, we consider a case in which the Kolmogorov scale is much smaller than the equilibrium correlation length ξ. Although equilibrium critical fluctuations are destroyed by turbulence, ξ still provides a crossover length scale between two types of energy cascade. At scales much larger than ξ, the Richardson cascade becomes dominant, whereas at scales much smaller than ξ, another type of cascade, which we call the van der Waals cascade, is induced by density fluctuations. Experimental conditions required to observe the van der Waals cascade are also discussed.